Industria televisiva en Pereira: una aproximación tendencial (2021)
The cultural industries are nowadays, the centre of multiple studies and researches. The present work is proposed with the object of searching about the current state of television producers in Pereira. This investigation work aims to present the perspectives in the audiovisual industry in the city, from an empiric-descriptive perspective which allows tracing a tendency in terms of the way in which these companies operate in terms of proceeding and at an individual level. In this way, some variables such as type of production of contents –classified in genders and formats-, number of hired people, production volume, technological support used by the companies for its operation, professional profile – in terms of academic tuition-, and time of experience in the area, are analyzed.